Antitumor Effects and Biological Mechanism of Action of the Aqueous Extract of the Camptotheca acuminata Fruit in Human Endometrial Carcinoma Cells. (21st May 2014) - Lin, Chi-Shian; Chen, Pin-Chien; Wang, Chien-Kai; Wang, Chia-Woei; Chang, Yu-Jia; Tai, Cheng-Jeng; Tai, Chen-Jei
Abstract : The aqueous extracts of the leaves and fruit of Camptotheca acuminata have long been used in traditional Chinese medicine (TCM) for treating cancer patients. The chemotherapeutic drug, camptothecin (CPT), and related analogs were first isolated from C. acuminata in the 1970s. Although the antitumor effects of CPT have been characterized in recent years, the antitumor effects of aqueous extracts of C. acuminata have not been clarified. The aims of our current study were to determine the tumor-suppression efficiency of an aqueous extract of the fruit of C. acuminata (AE-CA) in the human endometrial carcinoma cell lines, HEC-1A, HEC-1B, and KLE, and compare its antitumor effects with those of CPT. Cell viability assays indicated that a dosage of AE-CA containing 0.28 mg/mL of CPT demonstrated enhanced cytotoxicity, compared with CPT treatment. The effects of AE-CA on the induction of cell cycle arrest, the accumulation of cyclin-A2 and -B1, and the activation of caspase-3 and caspase-7 were similar to those of CPT. Furthermore, AE-CA exhibited a synergistic effect on the cytotoxicity of cisplatin in HEC-1A and HEC-1B cells. These results indicated that AE-CA is a potent antitumor agent and can be combined with cisplatin for the treatment of human endometrial cancer.